A Phenomenological Study on the Lived Experiences of SPED English Teachers in BARMM Region - Fernando R. Gallarde Jr.; Mark Dave D. Gatera; Lorenzo Buscato; Paul John Villaries (East Asian Journal of Multidisciplinary Research, 2022)
This research was conducted in the parameters of the Bangsamoro Autonomous Region in Muslim Mindanao (BARMM), Philippines. In order to determine the lived experiences of the special education teachers in the region, the study used a qualitative research design and a phenomenological approach. The participants of this study were five special education teachers, and the researcher used a semi-structured in-depth-interview in this study. Findings revealed that the special education teachers’ experiences during distance learning were extremely challenging, five themes emerge on the challenges encountered in teaching special education learners; these were mixed disabilities in one classroom, lack of comprehension, poor parental educational attainment, tantrum-inducing behavior, and inadequate funding and government support. Four themes that emerge on the coping strategies in addressing the challenges encountered in teaching English language to the special education learners. These were home visitation, K to 12 curriculum integration, educational mainstreaming, and individualized educational plan. The researchers concluded that teaching English to special education students is difficult, especially in this time of pandemic; it necessitates a significant amount of effort especially since the teacher is dealing with different disabilities in one classroom.